Clinical outcomes among unresectable, locally advanced, and metastatic cutaneous squamous cell carcinoma patients treated with systemic therapy. (24th June 2020) - Cowey, C. Lance; Robert, Nicholas J.; Espirito, Janet L.; Davies, Kalatu; Frytak, Jennifer; Lowy, Israel; Fury, Matthew G.
Abstract: Prior studies of conventional chemotherapy or epidermal growth factor receptor inhibitors for advanced (ie, locally advanced cutaneous squamous cell carcinoma [laCSCC] or metastatic [mCSCC]) cutaneous squamous cell cancer enrolled ≤ 40 patients. This retrospective, observational study assessed real‐world treatment patterns and clinical outcomes in patients with unresectable laCSCC or mCSCC using electronic health records of patients who initiated first‐line (1L) systemic treatment from 1 January 2008 to 31 December 2015, with follow‐up to 30 September 2017. The median duration of follow‐up from 1L treatment was 10.1 months (range 0.03‐67.6 months). Duration of therapy (DOT) and overall survival (OS) were assessed using Kaplan‐Meier analysis. Response rate was calculated as the proportion of patients who achieved physician‐assessed‐response. Eighty‐two patients were identified (17 laCSCC and 65 mCSCC). Median age at 1L treatment initiation was 75 years; 85% were male, 88% had an Eastern Cooperative Oncology Group performance status of 1, and 84% had received radiotherapy. The most common 1L regimens were carboplatin + paclitaxel (27%) and cetuximab monotherapy (24%). The median 1L DOT was 4.1 months for laCSCC and 2.3 months for mCSCC. The physician‐assessed response rate for 1L therapy was 17.6% for laCSCC, and 18.5% for mCSCC. The median OS from 1L treatment initiation was 16.2 months for laCSCC, and 15.3 months for mCSCC. Only 24 patients (29%) received second‐line therapy. This is the largest retrospective data set regarding patients with advanced CSCC treated with anticancer systemic therapy prior to approval of the anti‐programmed cell death‐1 antibody, cemiplimab. Efficacy was low in both laCSCC and mCSCC. These data provide historic benchmarks for outcomes in patients with advanced CSCC prior to Food and Drug Administration approval of cemiplimab‐rwlc. Abstract : This retrospective study describes the limited efficacy of systemic therapy in a real‐world population of patients with locally advanced and metastatic cutaneous squamous cell carcinoma. The data provide historic benchmarks for outcomes of treatment for these patients prior to the approval of cemiplimab.